Determinación del efecto de progesterona inyectable previo al reconocimiento materno para mejorar el porcentaje de preñez en vacas - Castillo Yanchapaxi, Jhoel Ufredo (2024)
The use of progesterone in production cows in Ecuador, as well as in other countries, is used in breeding programs for the efficient reproductive improvement of cattle. The objective of the experimental work is to investigate the influence of the administration of injectable progesterone before maternal signaling in the relationship with the corpus luteum and its contribution to the pregnancy percentage in cows. It is known that progesterone played a crucial role in the preparation of the uterus for implantation and development of pregnancy. The experimental work was carried out with a completely randomized design "DCA" with 2 treatments from which two groups of cows were designated, which entered the IATF protocol, one group received an injection of 2 ml of progesterone, 16 days post insemination at a fixed time, while another group was assigned as a control group, later the pregnancy percentage was evaluated by ultrasound on specific days post-insemination. The results indicate that there is no significant difference between both treatments, but a 56.33% pregnancy rate was obtained in cows with injectable progesterone, which can be used as an alternative treatment, thus improving reproductive efficiency in bovine production systems. The cost-benefit analysis resulted in a total cost for the treatment group with injectable progesterone of $703.62 and a total cost for the control group without injectable progesterone of $668.58. Thus demonstrating that there is a difference of $35.04 between both treatments, this approach could be an effective strategy to improve fertility rates and productivity in livestock